2014
DOI: 10.1007/s11999-014-3696-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Procedure-specific Risk Factors for Deep Infection After Primary Shoulder Arthroplasty

Abstract: Background Deep infection after shoulder arthroplasty is a diagnostic and therapeutic challenge. The current literature on this topic is from single institutions or Medicare samples, lacking generalizability to the larger shoulder arthroplasty population. Questions/purposes We sought to identify (1) patientspecific risk factors for deep infection, and (2) the pathogen profile after primary shoulder arthroplasty in a large integrated healthcare system. Methods A retrospective cohort study was conducted. Of 4528… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(134 citation statements)
references
References 19 publications
5
122
1
1
Order By: Relevance
“…We did not perform deep cultures because other authors have demonstrated positive deep cultures in revision surgery. 8,19 Moreover, we believe deep cultures in primary surgery that grow P acnes should be considered with caution because it is difficult not to contaminate the deep tissues if P acnes is present within the wound from the time of skin incision, as has been shown in this study.…”
Section: Discussionmentioning
confidence: 62%
“…We did not perform deep cultures because other authors have demonstrated positive deep cultures in revision surgery. 8,19 Moreover, we believe deep cultures in primary surgery that grow P acnes should be considered with caution because it is difficult not to contaminate the deep tissues if P acnes is present within the wound from the time of skin incision, as has been shown in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown inconsistent results regarding the association of obesity on complications in upper extremity arthroplasty [3,5,13,14,27,31]. Some smaller reviews have reported an increase in associated complications [3,5,14], whereas studies with larger sample sizes have shown no such relationship [13,27,31]. In a review of reverse TSAs, Beck et al [5] found that the coexistence of obesity was associated with increased complications.…”
Section: Discussionmentioning
confidence: 99%
“…Male gender is a risk factor associated with P. acnes PJI [30,57,65,68], presumably due to the presence of a higher number of pilosebaceous glands and hair follicles in men compared to women. In one study, men who underwent shoulder prosthesis placement were found to be over 2.5 times more likely to develop PJI than women; the most commonly cultured organism in this cohort was P. acnes [70]. This same analysis identified younger age as a risk factor, with each additional year of age resulting in a 5% risk reduction for PJI [70].…”
Section: Risk Factorsmentioning
confidence: 93%
“…In one study, men who underwent shoulder prosthesis placement were found to be over 2.5 times more likely to develop PJI than women; the most commonly cultured organism in this cohort was P. acnes [70]. This same analysis identified younger age as a risk factor, with each additional year of age resulting in a 5% risk reduction for PJI [70]. Likely, this is due to the increased activity of the sebaceous glands, secondary to increased androgen production during puberty [71].…”
Section: Risk Factorsmentioning
confidence: 97%